Jain point laparoscopic entry in contraindications of Palmers point - Jain, Nutan; Srivastava, Sakshi; Bayya, Sri Lakshmi Prasanna; Jain, Vandana (Frontiers in Surgery, 2022)
Abstract: Background: Being at mid abdomen can be used for entry when previous surgical scars are in upper abdomen. To tide over contraindications of Palmer’s point, we devised Jain point on the left side of the abdomen at L4 level, 10–13 cm lateral to the umbilicus. The rationale for Jain point being free of adhesions is that post-surgical adhesions are encountered usually in midline or right side; the left side of the abdomen is spared as stomach, kidney, and spleen lie higher up at T10 – L1 level and lower down sigmoid colon adheres at pelvic brim; leaving a large nascent area between them which is free of adhesions. Methods: This is a retrospective study conducted at a high-volume tertiary care referral center for advanced gynecological laparoscopic surgery enrolling 8586 patients who underwent laparoscopy at our center between January 2011 and March 15, 2022, to assess the safety and feasibility of a new laparoscopic entry port, Jain point, in previous surgery cases to tide over contraindications of Palmer’s point. In this paper, we analyzed 2519 patients with a history of previous surgeries. All patients were entered by Jain Point in an identical manner. Results: Jain point port being at mid abdomen far lateral, was found to be adhesion free, regardless of the scars, numbers, and type of previous surgeries. No major complication reported apart from one case of bowel injury which was managed intraoperatively. Jain point is equally applicable for scars in upper, mid, and lower abdomen where as Palmer’s point is contraindicated in upper abdomen scars which are in midline or on left side. Palmer’s point becomes redundant after initial entry, whereas Jain point continues as main ergonomic working port. We used Jain Point entry in all contraindications of Palmer’s point. Conclusion: Jain Point offers an alternate safe entry port in previous surgery cases and this paper highlights it as a viable option in the contraindications of Palmer’s point.